Current Concepts for Classification and Treatment of Distal Clavicle Fractures - Kim, Dong-Wan; Kim, Du-Han; Kim, Beom-Soo; Cho, Chul-Hyun (Clinics in orthopedic surgery, 2020)
Distal clavicle fractures are less common than mid-shaft fractures in adults and there is no consensus on the best classification system or the ideal treatment approach considering that high nonunion rates have been reported. Although there are numerous treatment options for distal clavicle fractures, a gold standard treatment has not yet been established. Each surgical technique has its pros and cons. In this review article, we provide an overview of classification systems and treatment methods for distal clavicle fractures.Distal clavicle fractures are less common than mid-shaft fractures in adults and there is no consensus on the best classification system or the ideal treatment approach considering that high nonunion rates have been reported. Although there are numerous treatment options for distal clavicle fractures, a gold standard treatment has not yet been established. Each surgical technique has its pros and cons. In this review article, we provide an overview of classification systems and treatment methods for distal clavicle fractures.